Environmental Externalities of Geological Carbon Sequestration Effects on Energy Scenarios - Bob van der Zwaan; Koen Smekens (Fondazione Eni Enrico Mattei (FEEM), 2004)
Geological carbon sequestration seems one of the promising options to address, in the near term, the global problem of climate change, since carbon sequestration technologies are in principle available today and their costs are expected to be affordable. Whereas extensive technological and economic feasibility studies rightly point out the large potential of this clean fossil fuel' option, relatively little attention has been paid so far to the detrimental environmental externalities that the sequestering of CO2 underground could entail. This paper assesses what the relevance might be of including these external effects in long-term energy planning and scenario analyses. Our main conclusion is that, while these effects are generally likely to be relatively small, carbon sequestration externalities do matter and influence the nature of future world energy supply and consumption. More importantly, since geological carbon storage (depending on the method employed) may in some cases have substantial external impacts, in terms of both environmental damage and health risks, it is recommended that extensive studies are performed to quantify these effects. This article addresses three main questions: (i) What may energy supply look like if one accounts for large-scale CO2 sequestration in the construction of long-term energy and climate change scenarios; (ii) Suppose one hypothesizes a quantification of the external environmental costs of CO2 sequestration, how do then these supposed costs affect the evolution of the energy system during the 21st century; (iii) Does it matter for these scenarios whether carbon sequestration damage costs are charged directly to consumers or, instead, to electricity producers?
Keywords: O33; O38; Q43; 330; Geological carbon storage; External costs; Energy scenarios; Treibhausgas-Emissionen; Externer Effekt; Klimaschutz; Energieprognose; Welt